Tracheal diverticulum: a rare entity - Agarwal, Abhishek; Kathuria, Sudhanshu; Sharma, Rachit; Khanduri, Sachin (International Journal of Advances in Medicine, 2017)
Tracheal diverticulum is a rare entity usually found incidentally on CT thorax or post-mortem. We are here describing an interesting case of a 28 year old male who presented to us with hemoptysis and symptoms of lower respiratory tract infection and was found to have tracheal diverticulum on further evaluation by CT thorax and fibreoptic bronchoscopy.